Geodesic acoustic mode evolution in L-mode approaching the L–H transition on JET. (29th May 2019) - Silva, C; Hillesheim, J C; Gil, L; Hidalgo, C; Maggi, C F; Meneses, L; Solano, E R
Abstract: Geodesic acoustic modes (GAMs) may generate strong oscillations in the radial electric field and therefore are considered as a possible trigger mechanism for the L–H transition. This contribution focuses on the characterization of GAMs in JET plasmas when approaching the L–H transition aiming at understanding their possible role in triggering the transition. GAM and turbulence characteristics are measured at the plasma edge using Doppler backscattering for different plasma current and line-averaged densities. The radial location of the GAM often moves further inside when neutral beam injection is applied possibly as a response to changes in the turbulence drive. GAMs are found to have modest amplitude at the transition except for high density discharges where GAMs are stronger, suggesting that the GAM is not responsible for facilitating the transition as the L–H power threshold also increases with density in the high density branch of the L–H transition. Our results suggest that the GAM alone does not play a leading role for causing the L–H transition at JET.